HOW DOES INNOVATIVE LEADERSHIP DEVELOPMENT AND PERCEIVED ORGANIZATIONAL SUPPORT ON HUMAN RESOURCE THROUGH MANAGEMENT COMPETENCIES IN BUDDHIST COLLEGE LECTURERS ACROSS INDONESIA? - Ardianto , Hendry; Nagatirtha, Partama; Burmansah , Burmansah; Suryanadi , Juni (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Human resource (HR) is becoming an increasingly important component of the entire strategy and operations of organizations in a variety of sectors and the rapidly changing educational environment. Quality improvement will be realised when they have in-depth knowledge, relevant skills and a positive attitude toward their duties and responsibilities. This research aims to determine the influence between the development of innovative leadership, perceived organizational support and management competencies on improving human resources. This research was coducted at 12 Buddhist Universities in Indonesia. This study takes a quantitative approach, employing a survey method and path analysis with SPSS 26. The unit of analysis in this study was PTKB Lecturers across Indonesia. Data were collected through questionnaires. The sampling approach used simple random sampling.The sample in this study amounted to 154 lecturers. Samples were collected from a total of 250 PTKB lecturers across Indonesia.